ANALISIS PENGARUH PEMBAYARAN DEVIDEN TERHADAP HARGA SAHAM SYARIAH DI JAKARTA ISLAMIC INDEX - wahid, abdul; Rahma, Syahidah (Jurnal Ar-Ribh, 2019)
This study aims to determine the effect of Dividend Per Share payments on Stock Prices Closing Price of Manufacturing Companies in the Jakarta Islamic Index. The population in this study were all manufacturing companies included in the Jakarta Islamic Index (JII) of the Indonesia Stock Exchange for 5 years from 2011-2015 which actively published financial reports during the year of observation. The method used in this study is the documentation method, then in analyzing the data used to test the matched hypothesis, namely by quantitative descriptive analysis. Based on the results of the analysis, it can be seen that there is no relationship between the Dividend Per Share on changes in stock prices, this can be seen in PT.ASII during 2012 to 2014, it appears that the Dividend Per Share at PT.ASII has not changed for three years, while the share price always changes for three years. It is also seen in PT. AVR, it is seen that the Dividend Per Share for the past five years has always changed and fluctuated, meanwhile the stock price continued to increase from year to year without following the fluctuations that occurred in the Dividend Per share.